2013
DOI: 10.1063/1.4801496
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printing of aligned single-walled carbon-nanotube thin films

Abstract: We report a method for the inkjet printing of aligned single-walled carbon-nanotube (SWCNT) films by combining inkjet technology with the strong wettability contrast between hydrophobic and hydrophilic areas based on the patterning of self-assembled monolayers. Both the drying process control using the strong wettability boundary and the coffee-stain effect strongly promote the aggregation of SWCNTs along the contact line of a SWCNT ink droplet, thereby demonstrating our achievement of inkjet-printed aligned S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…CNTs are a promising candidate for printed electronics, offering stable high‐performance devices . Techniques such as inkjet and gravure printing can be used to print CNT inks. In general, both metallic and semiconducting CNTs exist in the films, and hence the on/off ratio decreases with the channel length, because the metallic CNTs can bridge the short‐channel region .…”
Section: Methodsmentioning
confidence: 99%
“…CNTs are a promising candidate for printed electronics, offering stable high‐performance devices . Techniques such as inkjet and gravure printing can be used to print CNT inks. In general, both metallic and semiconducting CNTs exist in the films, and hence the on/off ratio decreases with the channel length, because the metallic CNTs can bridge the short‐channel region .…”
Section: Methodsmentioning
confidence: 99%
“…Other ways to pattern the CNT‐LC is by using a substrate patterned with different wettability (both hydrophilic and hydrophobic) for CNT‐LC or substrates placing in a wedge configuration . With self‐assembled monolayer (SAM) together with inkjet printing, it has been shown that aligned CNTs thin film can be produced using strong wettability boundary and coffee‐stain effect . It was found that CNTs lines with smaller line width can have better CNTs alignment .…”
Section: Mechanisms Of Cnts Alignmentmentioning
confidence: 99%
“…[551][552][553][554] The printed CNT networks are used as channel materials, and rapid progress has been achieved on the separation of metallic and semiconducting CNTs, [362,364] and deposition of well-aligned CNTs channels along the sourceto-drain direction. [555,556] For example, Jang et al fabricated short-channel (150-200 nm) FET using inkjet printing of semiconducting CNTs, [557] which exhibited a mobility value of 24 cm 2 V À1 s À1 at an operation voltage of 0.5 V. The doped CNTs (p type and n type CNTs) have also been used to fabricate CMOS devices. [558,559] Kim et al fabricated ICs using ambipolar and p-type single-walled CNT thin-film transistors.…”
Section: D Inorganic Semiconductorsmentioning
confidence: 99%